FINANCIAL PERFORMANCE EVALUATION OF BANK: CASE STUDY AT THE BANK OF INDONESIA, Tbk - Paramita, Ken Dessa; Indrayani, SE., MM, DR. Emmy (Accounting, 2009)
The financial statements (financial statements) is an overview of the financial condition of a bank at a certain period. Balance (balance sheet) of a bank described the amount of wealth (assets), liabilities (debts), and the capital of the bank at any given moment. Balance sheet is usually compiled at the end of the financial year (31 December). Wealth or property is presented on the asset while the liability or debt and equity are presented on the liabilities side. Consolidated profit / loss have also been prepared at the end of the financial year. The financial statements represent a continuous history which quantified in units of currency with respect to economic resources and obligations of a company´s business and economic activities that alter these resources and liabilities, (AICPA, 1970, p. 40) Information about the company´s financial position, company performance, corporate cash flow, and other information relating to the financial statements may be obtained from the company´s financial statements. To understand information about financial statements, financial statement analysis is needed (Gibson and Boyer, 1980). Analysis of the financial statements include the calculation and interpretation of financial ratios. Techniques of financial analysis is intended to show the relationship between existing posts in the financial statements so that can know the changes that occur in these posts. The purpose of the analysis technique is to present the data to be more easily understood and well understood. To analyze the financial performance of the specific measures required as a standard. Size is often used as an analytical tool is a ratio that shows the relationship between financial data. Keywords : financial performance, bank